Is Low Income Associated with Malocclusion in Primary Dentition Among Preschoolers? - Jessa Iashmin Alcobaça Gomes Machado; Natália Silva Andrade; Renara Natália Cerqueira Silva; Marcus Vinícius Nunes Neiva do Rego; Lúcia de Fátima Almeida de Deus Moura; Wagner Leal de Moura; Marina de Deus Moura de Lima (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the prevalence and factors associated with malocclusion in the primary dentition of preschool children in a city of Brazilian Northeast. Material and Methods: A cross-sectional study was conducted with 566 five-years-old preschool children who were enrolled in public and private preschools in the city of Teresina, Piauí, Brazil. Data were collected using a sociodemographic questionnaire administrated to parents/caregivers and clinical oral examination of the children was performed. Foster and Hamilton Index for primary teeth was used for the diagnosis of malocclusions. Descriptive analysis was carried out and Poisson regression was used to assesses the association with independent variables. Results: The prevalence of malocclusion was 51.2%. The most frequent types were Class II canines (17% and 16.8%), increased overjet (15.2%) and reduced overbite (14%). Anterior crossbite was present in 3.5% of the preschool children evaluated. There was an association between malocclusion and low family income (PR = 1.22; 95% CI = 1.01-1.47). Conclusion: The prevalence of malocclusion in the primary dentition was high and associated with a low family income.